Analysis Of Asn Core Value (BerAKHLAK) And Intrinsic Motivation On Asn Performance Through Organizational Commitment As An Intervening Variable At The Bkpsdm Of Langsa City - Putra Anshari; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of the ASN Core Values BerAKHLAK and Intrinsic Motivation on ASN Performance, with Organizational Commitment as a mediating variable at BKPSDM of Langsa City. This research employs a quantitative approach using the Partial Least Squares (PLS) method. The research sample consisted of 65 respondents who are State Civil Apparatus (ASN) working at the BKPSDM of Langsa City. The results show that the ASN Core Values BerAKHLAK have a positive and significant effect on ASN Performance (β = 0.694; p = 0.000) and on Organizational Commitment (β = 0.558; p = 0.001). Organizational Commitment also has a positive and significant effect on ASN Performance (β = 0.158; p = 0.034). Meanwhile, Intrinsic Motivation significantly affects Organizational Commitment (β = 0.321; p = 0.046) but does not have a significant effect on ASN Performance (β = 0.108; p = 0.228). The indirect effects through Organizational Commitment, both in the paths ASN Core Values → Organizational Commitment → ASN Performance (p = 0.074) and Intrinsic Motivation → Organizational Commitment → ASN Performance (p = 0.121), were found to be insignificant. The R-Square values indicate that ASN Performance is explained by the research variables by 87.0%, while Organizational Commitment is explained by 74.1%, demonstrating strong predictive power. This study emphasizes that implementing BerAKHLAK values and strengthening Organizational Commitment play vital roles in enhancing ASN Performance, whereas Intrinsic Motivation requires further reinforcement through effective managerial strategies.